Prevalence of geographic tongue on students of SD Saraswati 2, Denpasar : Prevalensi geographic tongue pada murid SD Saraswati 2, Denpasar - Intan Kemala Dewi; NI Nyoman Gemini Sari; I Gusti Ngurah Rai Diky Dermawan (Makassar Dental Journal PDGI Makassar, 2021)
Geographic tongue is a disorder which appears on the tongue in the form of an asymptomatic lesion, but its existence is rarely known, thus the prevalence of this disorder tends to be low. This disorder is strongly suspected to be influenced by genetic fac-tors and other predisposition factors. Several studies have revealed that this lesion occur more frequently on women than on men. The purpose of this research is to determine the prevalence of geographic tongue, based on the age and gender, among the stu-dents in SD Saraswati 2 Denpasar. The research is conducted using the descriptive epidemiology research method, and the re-sults attained are presented in a table and explained descriptively. The samples are all students from the 1st grade until the 6th grade with an overall total of 584. The research results show that the prevalence of the geographic tongue disorder is 28 people (4.80%). There were 15 girls (5.17%) who were afflicted, while there were 13 boys (4.42%). This disorder appeared most in the age group of 7 years old. This study found that 3 people (0.51%) claimed there are symptoms or pain, while the remaining 25 people (4.28%) do not show any symptoms or pain.